Representations, access to justice and voice for women of younger and older generations - Manuela Graciela González; Hilda Gabriela Galletti (Oñati Socio-Legal Series)
We start from the voices of women who go through situations of violence, their representations and access to justice, taking their particularities and difficulties in each period of life. We ask ourselves: How can we work better together from Legal Sociology to address these challenges interdisciplinary? How diverse must our justice institutions be to respond to the needs of women of different generations? How are the youngest girls given a voice in decisions about their future and in resolving their conflicts? The Administration of justice does or does not provide answers to women, they are adequate/inadequate according to the evolutionary moment and the conflicts they experience. To carry out this approach we will return to the concepts of governmentality, captivity and intersectionality, considering women as historical and cultural subjects.